Effectiveness of Different Types of Traps For Management of Tuta absoluta in Nepal - Kadel, Jyoti; Sah, Lalit P.; Devkota, Mukti; Colavito, Luke A.; Norton, George; Rajotte, Edwin George; Muniappan, Rangaswamy (Journal of the Plant Protection Society, 2018)
Among the various potential vegetables, tomato is one of the high value crops, with growing market demand and higher level of return per hector. South American Tomato leaf miner, Tuta absoluta is one of the main constrains in tomato production in Nepal. Field experiments were conducted from June to October 2017 to determine the attractive action of trap colours against T. absoluta management in Lele VDC, Lalitpur, Nepal. Experiments were setup using different types of traps (Delta trap, Wota-T trap and solar light trap) each with pheromone capsule i.e. TLM lure. Particularly, in this experiment the influence of color (orange, white, yellow and green) in delta trap, height adjustment from ground level - 1 feet, 2 feet, 3 feet and 4 feet) in Wota-T trap and; locally prepared light traps of led bulb, solar light trap with high power of 65 lumens and solar light trap with low power of 25 lumens to capture Tuta moth were tested. For the evaluation of effectiveness of different types of traps, number of Tuta moths captured were recorded. The results demonstrated that T. absoluta moths can distinguish between the colours. White colored delta trap captured maximum mean number of Tuta moth (22) followed by green (16), yellow (13) and orange (10). Similarly, Wota- T trap when placed at different height, trap placed at ground level captured maximum mean number of Tuta moths (15) followed by One ft (12), Two ft(11), Three ft(8) and Four ft(2). Among the different types of light trap solar light trap with high power of 65 lumens captured maximum mean number of Tuta moth’s (5) followed by solar light trap with low power of 25 lumens (3) and locally prepared light trap with led bulb (2). Significant differences between mean moth catches by different colored delta traps, wota-T trap placed at different height and different types of light traps were observed. Based on the study conducted with in a season it were found that trap color, trap height and light trap types are the characteristics that strongly affect the response of T. absoluta moths to pheromone-baited traps. From the study it is clear that, these traps can be used as one of the best sex pheromone based management strategy for the management of T. absoluta moths. Further research is recommended for better understanding of the effect of trap colour on the diversity and abundance of non target insects captured